Efficacy of Feed Additives Against Swine Viruses in Feed - G. E. Nichols; J. T. Gebhardt; C. K. Jones; J. C. Woodworth; S. S. Dritz; J. Bai; J. W. Anderson; E. Porter; F. B. Sandberg; A. Singrey; C. B. Paulk (Kansas Agricultural Experiment Station Research Reports, 2020)
Research has demonstrated that swine viruses can be transmitted via feed. Therefore, strategies are needed to prevent or mitigate swine viruses in feed. The use of chemical feed additives is a strategy that has been shown to have potential utility for this purpose. Therefore, the objective of this study was to evaluate the efficacy of a commercially available formaldehyde-based feed additive, medium chain fatty acid blend (MCFA), and commercially available fatty acid-based products for mitigation of porcine epidemic diarrhea virus (PEDV) and porcine reproductive and respiratory syndrome virus (PRRSV) as viral mitigants in a feed matrix. Experimental treatments consisted of: 1) non-treated, individually inoculated virus controls (positive control); 2) 0.33% commercial formaldehyde-based product (Sal Curb; Kemin Industries, Inc.; Des Moines, IA); 3) 0.50% MCFA blend (1:1:1 ratio of C6:0, C8:0, and C10:0, Sigma Aldrich, St. Louis, MO); 4) 0.25%; 5) 0.50%; or 6) 1.00% of commercial dry mono and diglyceride-based product (Furst Strike; Furst-McNess Company, Freeport, IL); 7) 0.25%; 8) 0.50%; or 9) 1.00% of commercial dry mono and diglyceride-based product (Furst Protect; Furst-McNess Company, Freeport, IL); 10) 0.25%; 11) 0.50%; or 12) 1.00% dry mono and diglyceride-based experimental product (Furst-McNess Company, Freeport, IL). In total there were 12 treatments with 3 replications per treatment. A complete swine feed was treated with each chemical treatment before inoculation with 106 TCID50/g of feed with PEDV or PRRSV. Post-inoculation feed was held at ambient temperature for 24 h before being analyzed via quantitative real time reverse transcription PCR (qRT-PCR). The analyzed values represent the cycle threshold (Ct). A lower Ct value indicates a higher level of detectable viral nucleic acid. Formaldehyde and MCFA decreased (P<0.05) the detectable RNA concentration of PEDV and PRRSV compared to all other treatments. Furst Strike, Furst Protect, and the experimental product did not significantly reduce detectable concentrations of RNA for PEDV or PRRSV. In conclusion, MCFA and formaldehyde chemical treatments are effective at reducing nucleic acid levels of PEDV and PRRSV in feed.
Keywords: phytase; pellet quality; phytase stability